Persepsi Mahasiswa FISIP USU Terhadap Gaya Kampanye Politik Prabowo–Gibran 2024 - Azzahra, Rahel Farhanah; Anshori, Akhyar (Universitas Muhammadiyah Sumatera Utara, 2024)
Political campaign style is one of the strategies and plans in building the image and branding of candidate pairs. Prabowo-Gibran's campaign style has received quite a bit of attention from students. Where, students are one group of people who have the potential to become voters and are quite active in following political developments. The aim of this research is to find out and explain USU Political and Social Sciences students' perceptions of the 2024 Prabowo-Gibran campaign style. This research uses quantitative research methods with descriptive analysis using validity, reliability, simple regression tests and hypothesis testing techniques. The results of the research show that there is no influence on students' perceptions of the Prabowo - Gibran 2024 political campaign style. Significance value from the tablecoefficients obtained a significance value of 0.504 0.05 andtcount 0,672 ttable1,98932, so it can be concluded that variable X has no effect on variable Y, thus H0 accepted and H1 rejected. So student perceptions have no influence on the Prabowo – Gibran 2024 campaign style